Paradigma Deep Ecology dalam Filsafat Lingkungan dan Implikasinya terhadap Pembangunan di Indonesia - Syaibatul Hamdi; Syahrul Hasan; Rahmat Salam; Andriansyah Andriansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study discusses the paradigm of deep ecology in environmental philosophy and its implications for sustainable development in Indonesia. The main problems faced by Indonesia are massive exploitation of natural resources, deforestation, pollution, and loss of biodiversity, which are triggered by an anthropocentric development model that focuses on economic growth. The objective of this study is to analyze how the principles of Deep Ecology can offer a more holistic and non-anthropocentric ethical framework to address the environmental crisis in Indonesia. The method used is a narrative literature review, analyzing various sources to explore the concept of deep ecology and its relevance in the Indonesian context. The main findings show that the application of deep ecology principles can encourage a paradigm shift in Indonesia's development policies, from exploitation to harmonious coexistence with nature. The implications of this research include the integration of ecocentric values in development planning and increased environmental awareness in society.